A Need Analysis of ESP for Physical Education Students in Indonesia - Budi Eko Pranoto; Suprayogi Suprayogi (Premise: Journal of English Education and Applied Linguistics, 2020)
This research aims at constructing the ideal English material for Physical Education students of universities in Lampung. Currently, students at university are taught about general English and it stimulates the writers to conduct a research to reveal their need of ESP as the answer of the current issues. This research is conducted in two universities, namely Universitas Teknokrat Indonesia and Universitas Lampung. The participants are 50 students, and 10 lecturers of Physical Education study program from both respective universities. The data are in the form of qualitative data which are taken from the interview and the questionnaire to students and lecturers which cover topics needed, and teaching method. The findings reveal the Physical Education students need of ESP in varied range of topics. The highly desired topics are English for sport journalism, English for professional athlete/referee/coach. Furthermore, based on the perspective of lecturers, they believe that students speaking, and writing must be well developed in order to compete in international level as professional athlete, coach, journalist, and etc. The result of analysis concludes the importance of ESP for Physical Educations students. Further research shall be conducted to test the effectiveness of the English topics constructed based on this current research.